Relationship between swimming start, turn and finish on final race time in 200m events - Mckenna, M.; Campbell, A.; Sheath, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
In competitive swimming, there has been increasing interest from swimmers, coaches and practitioners in the role played by the start, turn(s) and finish in the context of the overall outcome of a race (Morais et al., 2018). The aim of this study was to firstly compare the start, turn and finish times, for both male and emale swimmers, across all four swimming strokes for 200m events in national and international long-course-metre competitions. The secondary aim was to investigate the relationship between these different components of the race and final race time. The findings from this study seek to provide insights that could help guide training interventions and optimise race strategies for swimmers at different competitive levels and swimming strokes.